A Case Report of Thyroid Aplasia Misdiagnosed as Failure to Thrive - I. O. Oluwayemi; E. O. Adeniji; T. O. Ayeni (Highlights on Medicine and Medical Research Vol. 13, 2021)
Thyroid aplasia, a form of thyroid dysgenesis, is the most common cause of congenital hypothyroidism. Congenital hypothyroidism is one of the most preventable causes of mental retardation. The diagnosis of congenital hypothyroidism is challenging in our environment because of delay in diagnosis despite its debilitating effect on the intellectual development. We present a 10 year old girl who has been managed for failure to thrive, secondary to acyanotic congenital heart disease in the first year of life but later discovered on further evaluation to have congenital hypothyroidism (thyroid aplasia). She has since been on Levo thyroxine with remarkable linear growth but significant neurocognitive impairment.